PERSEPSI MAHASISWA ARSITEKTUR UPN VETERAN JAWA TIMUR PADA TERMINOLOGI RUANG DAN DESAIN ARSITEKTURAL - Ajeng Ajeng; Endang Sholihatin; Nindira Novilia (Jurnal Genta Mulia, 2024)
This research was conducted with several objectives to be achieved in this research, among others: (1) to find out the use of language and terminology that can affect individual perceptions in understanding, interpreting, and feeling a space in architectural design; (2) to find out the influence of language on the creation of space design so as to form an understanding of aesthetic preferences and feelings that arise towards architectural design elements; (3) to find out the use of language between architects, clients, and end users that affect design results and user understanding of a space, (4) the impact of differences in language use by end users in producing perceptions and interpretations of a space and architectural design. This research method uses mixed methods, namely field observation with qualitative methods and data collection through respondent questionnaires with quantitative methods. The conclusions in this study:  (1) It can be more effective in communicating an understanding of an architectural design in general, for example "modern" and "good"; (2) That the influence of language is very significant on an architectural design because based on the data obtained an effectiveness in language can affect the user's experience and perception of a space and architectural design; (3) In communication, we can use a language that is common and easily understood by two or more parties so that there are no misunderstandings or misperceptions; (4) The use of inappropriate language can have a negative impact, because if the use of language that is too complex will make it difficult for the other party to understand.